Positive electrode material and preparation method thereof, positive electrode sheet, secondary battery and electric device
By constructing a passivation layer of spinel and carbon layer on the surface of the positive electrode material, the problem of shortening the life of the positive electrode material under high pressure and low cobalt content is solved, and a higher energy density and longer cycle life is achieved.
Patent Information
- Application Number
- CN202211299012.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-21
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2042-10-21
AI Technical Summary
Under high pressure and low cobalt content, existing cathode materials are prone to surface phase change and lithium-nickel mixed discharge problems, resulting in shortening of life and unable to meet high energy density and power requirements.
A layered positive electrode material body is used, and a passivation layer is constructed on its surface, including a spinel layer and a carbon layer stacked in sequence from the inside to the outside, and a complete passivation layer is formed by ball milling mixing and calcining.
Effectively prevent electrolyte erosion, improve resistance to high pressure, reduce oxygen release and surface phase change, extend the life of the positive electrode material, and alleviate the growth of DC impedance.
Smart Images

Figure CN115832246B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of batteries, and in particular to a positive electrode material and a preparation method thereof, a positive electrode sheet, a secondary battery and an electrical device. Background Art
[0002] Positive electrode materials are an important component of lithium-ion batteries. The preparation of positive electrode materials with high safety performance, high specific capacity and stable cycle performance has an important impact on the development and application of lithium-ion batteries. In order to further improve energy density and reduce costs, positive electrode materials are developing in the direction of high voltage and low cobalt content. However, increasing the operating voltage accelerates the side reactions on the surface of the positive electrode material and the release of lattice oxygen, while reducing the cobalt content will lead to an increase in lithium-nickel mixing. The combined effect of the two will aggravate the problems such as cathode surface phase change during the cycle and storage process of the high-voltage and low-cobalt system, seriously affecting the life of the positive electrode material, and failing to meet the energy density and power requirements of the battery cell in the later stage of use. Summary of the invention
[0003] The main purpose of this application is to propose a positive electrode material and a preparation method thereof, a positive electrode plate, a secondary battery and an electrical device, aiming to alleviate the phase change on the surface of the positive electrode material and improve the life of the positive electrode material.
[0004] In a first aspect, the present application provides a positive electrode material, comprising: a layered positive electrode material body and a passivation layer coated outside the layered positive electrode material body, wherein the passivation layer comprises a spinel layer and a carbon layer stacked sequentially from inside to outside.
[0005] In the technical solution of the embodiment of the present application, defects are constructed on the surface of the layered positive electrode material body to construct a passivation layer, which includes a high-voltage resistant spinel layer and an outermost carbon layer, to protect the layered positive electrode material body, better prevent the electrolyte from corroding the positive electrode material, improve resistance to high voltage, reduce oxygen release and surface phase change, alleviate the phase change on the surface of the positive electrode material, and ultimately extend the life of the positive electrode material and alleviate the increase of DC impedance.
[0006] In some embodiments, the material of the layered positive electrode material body includes LiMO2 or xLi2MnO3·(1-x)LiMO2, wherein M is at least one of Mn, Co, Ni, Fe, Al, Nb, Ti, Zr, W, V, Ta, Mo, Sb and La, and 0≤x≤1.
[0007] The above materials have the advantages of high specific capacity (up to 3005Ah / g) and low cost, and are ideal for high energy density power lithium batteries.
[0008] In some embodiments, the carbon content in the positive electrode material is 0.02wt.% to 3.20wt.%. Under the above content, the carbon layer has a moderate thickness, which can better prevent the electrolyte from corroding the positive electrode material, improve the resistance to high voltage, reduce oxygen release and surface phase change, and alleviate the phase change on the surface of the positive electrode material, ultimately extending the life of the positive electrode material and alleviating the increase of DC impedance.
[0009] In a second aspect, the present application provides a method for preparing a positive electrode material, comprising the following steps:
[0010] S10, mixing the layered cathode material body and the carbon source to obtain an intermediate;
[0011] S20, calcining the intermediate to obtain a positive electrode material.
[0012] The carbon source is selected and mixed with the positive electrode material to ensure that the positive electrode material particles are completely coated, and a more complete and dense passivation layer is formed after calcination, which has a better performance improvement effect.
[0013] In some embodiments, in step S10, the carbon source includes a long-chain organic acid. With the long-chain organic acid as the carbon source, the carbon layer is formed to be more dense and stable.
[0014] In some embodiments, the long-chain organic acid includes at least one of stearic acid, oleic acid, linoleic acid, linolenic acid, palmitic acid and arachidonic acid. Experiments show that the use of the above organic matter as a carbon source enables the carbon source to be completely coated on the surface of the positive electrode material particles, thereby forming a more complete and dense passivation layer after calcination, and it is also easier to form a carbon layer.
[0015] In some embodiments, in step S10, the mass ratio of the layered cathode material body to the carbon source is 90:10 to 99:1.
[0016] When the carbon source ratio is too high during mixing, the passivation layer formed is too thick, which will lead to deterioration of the initial kinetic performance; if the carbon source ratio is too low, the passivation film formed is insufficient and cannot effectively protect the surface of the positive electrode material. When the mass ratio of the layered positive electrode material body to the carbon source is 90:10 to 99:1, the thickness of the passivation layer is moderate.
[0017] In some embodiments, in step S10, the mass ratio of the layered cathode material body to the carbon source is 98:2 to 95:5. Under the above conditions, the thickness of the passivation film is the best.
[0018] In some embodiments, step S10 includes:
[0019] The layered cathode material body and the carbon source are mixed, a grinding aid is added, the mixture is ball-milled, and then dried to obtain an intermediate.
[0020] Adding a grinding aid can increase the fluidity of the carbon source during ball milling, help the carbon source and the positive electrode material to mix better, and ultimately form a complete covering organic acid polymer coating layer on the layered positive electrode material body, thereby obtaining a more complete passivation layer after calcination.
[0021] In some embodiments, the ball milling time is 3 to 7 hours; further, the ball milling time is 3 to 5 hours; under the above ball milling time, a completely covering organic acid polymer coating layer can be formed on the layered positive electrode material body.
[0022] In some embodiments, the grinding aid includes at least one of alcohol, acetone, benzene and ether; and / or the mass ratio of the carbon source to the grinding aid is 95:5 to 99.5:0.5.
[0023] The grinding aid includes at least one of alcohol, acetone, benzene and ether, and the grinding aid effect is better.
[0024] In some embodiments, the mass ratio of the carbon source to the grinding aid is 99:1 to 97:3. Under the above ratio, the phase change on the surface of the positive electrode material can be best alleviated and the life of the positive electrode material can be improved.
[0025] In some embodiments, in step S20, the calcination is carried out in an air atmosphere; and / or, during calcination, the heating rate is 5 to 15°C / 5in; and / or, the calcination temperature is 400 to 700°C; and / or, the calcination time is 30 to 1205in.
[0026] The selection of calcination conditions is critical to the formation of the passivation film. If the calcination time is too long or the temperature is too high, the organic matter will be completely converted into carbon dioxide and the outermost carbon layer cannot be retained. If the calcination temperature is too low or the time is too short, the organic matter will not be completely calcined, which will deteriorate the interface performance.
[0027] In some embodiments, the calcination conditions are: in an air atmosphere, a heating rate of 10 to 13°C / 5in, keeping warm at a temperature of 500 to 600°C for 50 to 755in, and naturally cooling to obtain a surface passivated positive electrode material.
[0028] In a third aspect, the present application provides a positive electrode plate, comprising the positive electrode material in the above-mentioned embodiment.
[0029] In a fourth aspect, the present application provides a secondary battery, comprising the positive electrode plate in the above embodiment.
[0030] In a fifth aspect, the present application provides an electrical device, comprising the secondary battery in the above-mentioned embodiment. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0032] Figure 1 This is a scanning electron microscope image of the intermediate of Example 1 of the present application;
[0033] Figure 2 This is a scanning electron microscope image of the positive electrode material of Example 1 of the present application;
[0034] Figure 3 XRD diagrams of the positive electrode materials obtained in Example 1 and Example 13 of the present application;
[0035] Figure 4 This is a cycle data diagram of the positive electrode materials obtained in Examples 1 and 13 of the present application.
[0036] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0037] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0038] It should be noted that, in the embodiments, those without specifying specific conditions are carried out according to normal conditions or conditions recommended by the manufacturer. Those without specifying the manufacturer of reagents or instruments used are conventional products that can be purchased commercially. In addition, the meaning of "and / or" appearing in the full text includes three parallel schemes, and "A and / or B" is taken as an example, including schemes A, B, or A and B that meet the same time. In addition, the technical schemes between the various embodiments can be combined with each other, but must be based on the ability of ordinary technicians in the field to achieve. When the combination of the technical schemes is contradictory or cannot be achieved, it should be considered that the combination of such technical schemes does not exist, and is not within the scope of protection required by the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work, all belong to the scope of protection of the present invention.
[0039] At present, the lithium battery industry is developing rapidly, and cathode materials are an important component of lithium-ion batteries. The preparation of cathode materials with high safety performance, high specific capacity and stable cycle performance has an important impact on the development and application of lithium-ion batteries. In order to further increase energy density and reduce costs, cathode materials are developing towards high voltage and low cobalt content.
[0040] The inventors noticed that increasing the operating voltage accelerated the side reactions on the surface of the positive electrode material and the release of lattice oxygen, while reducing the cobalt content would lead to an increase in the mixing of lithium and nickel. The combined effect of the two would aggravate problems such as the cathode surface phase change during the cycle and storage process of the high-voltage, low-cobalt system, seriously affecting the life of the positive electrode material and failing to meet the energy density and power requirements of the battery cell in the later stages of use.
[0041] Based on the above analysis and searching the relevant technologies in the database, the relevant personnel have adopted layered positive electrode materials improved by organic acids. Among them, the inventors found after repeated experiments that the liquid phase method uses the positive electrode material as the raw material, stirs it in an organic long-chain acid (carboxylic acid, keto acid, hydroxy acid, aromatic), and after coating a layer of organic film on the positive electrode surface, it is further calcined in the air to obtain a surface-modified positive electrode material. However, this method needs to be filtered and dried after liquid phase treatment and then calcined. The process is complicated and the organic acid raw material is seriously wasted. The process needs to be improved before it can be applied in large-scale industrial production.
[0042] The solid phase method uses the precursor as the raw material, mixes the solid organic carbon source (sucrose, glucose, starch, citric acid) and the precursor by ball milling, and then calcines the mixture with lithium to obtain the surface treated cathode material. In this method, the carbon source and the cathode material are only in surface contact, and a good coating structure cannot be formed. Only a local island coating is formed, and the outermost carbon coating cannot be formed, so the improvement effect is not good.
[0043] In view of the above defects, the applicant has proposed a positive electrode material and a preparation method thereof after a lot of creative work. By mixing the positive electrode material and the carbon source through ball milling, and adding an organic grinding aid during ball milling and fully ball milling and calcining, a passivation layer can be obtained outside the layered positive electrode material body. The passivation layer includes a spinel layer and a carbon layer stacked in sequence from the inside to the outside. Compared with the prior art, the beneficial effects of the present application are:
[0044] Defects are constructed on the surface of the layered positive electrode material to construct a passivation layer, which includes a high-voltage resistant spinel layer and an outermost carbon layer, to protect the layered positive electrode material body, better prevent the electrolyte from corroding the positive electrode material, improve resistance to high voltage, reduce oxygen release and surface phase change, and alleviate the phase change on the surface of the positive electrode material, ultimately extending the life of the positive electrode material and alleviating the increase of DC impedance.
[0045] In some embodiments, the material of the layered positive electrode material body includes LiMO2 or xLi2MnO3·(1-x)LiMO2, wherein M is at least one of Mn, Co, Ni, Fe, Al, Nb, Ti, Zr, W, V, Ta, Mo, Sb and La, and 0≤x≤1.
[0046] The above materials have the advantages of high specific capacity (up to 3005Ah / g) and low cost, and are ideal for high energy density power lithium batteries.
[0047] In some embodiments, the carbon content in the positive electrode material is 0.02wt.% to 3.20wt.%. Under the above content, the carbon layer has a moderate thickness, which can better prevent the electrolyte from corroding the positive electrode material, improve the resistance to high voltage, reduce oxygen release and surface phase change, and alleviate the phase change on the surface of the positive electrode material, ultimately extending the life of the positive electrode material and alleviating the increase of DC impedance.
[0048] It can be understood that in the embodiment of the present invention, the carbon content is the mass fraction of the carbon element in the positive electrode material.
[0049] The inventors found that compared with the composite coating of inert oxides and fast ion conductor carbon on the positive electrode active material in the prior art, the composite passivation film is used in the present application, and the layered positive electrode material body adopts the above-mentioned material, which has more uniform properties on the one hand, and better conductivity on the other hand. It can avoid the contact between the positive electrode active material and the electrolyte, so that the positive electrode material has a lower surface impedance, thereby improving the cycle performance of the secondary battery and making the secondary battery have a longer cycle life.
[0050] The inventors have found that in the positive electrode material of the present application, the positive electrode active material is selected from the above-mentioned suitable materials, which can make the secondary battery have higher energy density, good cycle performance and long cycle life.
[0051] In a second aspect, the present application provides a method for preparing a positive electrode material, comprising the following steps:
[0052] S10, mixing the layered positive electrode material body and the carbon source to obtain an intermediate.
[0053] In this step, the layered cathode material body and the carbon source are mixed so that the carbon source can be completely coated on the surface of the cathode material particles.
[0054] In the embodiment of the present application, a long-chain organic acid is selected as a carbon source and mixed with the positive electrode material (layered positive electrode material body) by ball milling, which can ensure that the particles of the layered positive electrode material body are completely coated, and a more complete and dense passivation layer is formed after calcination, which has a better performance improvement effect. The long-chain organic acid has a high carbon content, a high boiling point, is easy to carbonize and is not easy to volatilize, and after carbonization, it is easier to adhere to the surface of the layered positive electrode material body to form a passivation layer.
[0055] Specifically, the long-chain organic acid includes at least one of stearic acid, oleic acid, linoleic acid, linolenic acid, palmitic acid and arachidonic acid. Stearic acid, i.e. octadecanoic acid, has a molecular formula of C 18 H 36 O2, produced by oil hydrolysis, is mainly used to produce stearate, widely available, and the raw materials are easy to obtain; Oleic acid molecular formula C 18 H 34 O2, heated to 80-100℃ under atmospheric pressure, decomposes and easily carbonizes to form a carbon layer; linoleic acid molecular formula C 18 H 32 O2, insoluble in water, soluble in most organic solvents, mainly used as raw materials for the production of paints and inks; Palmitic acid, also known as palmitic acid, scientific name hexadecanoic acid. Molecular formula: C 16 H 32 O2. It is a white scale with pearlescent luster, existing in the form of glyceride in many oils and fats. It is insoluble in water, slightly soluble in cold alcohol and petroleum ether, and soluble in hot ethanol, ether and chloroform. It is used to make candles, soaps, lubricants, synthetic detergents, softeners, etc. It can be obtained by hydrolysis of palm oil; Arachidonic acid (English: Arachidonic acid, all-cis-eight carbon-5,8,11,14-tetraenoic acid, 20:4Δ5c,8c,11c,14c) is a ω-6 polyunsaturated fatty acid, which is the counterpart of saturated arachidic acid in peanut oil; Linolenic acid is referred to as LNA, which belongs to the ω-3 series of polyene fatty acids (abbreviated as PUFA), which is all-cis-9, 12, 15 octadecadienoic acid, and it exists in dark green plants in the form of glyceride. The above organic matter is used as a carbon source, so that the carbon source can be completely coated on the surface of the positive electrode material particles, so that a more complete and dense passivation layer is formed after calcination, and it is also easier to form a carbon layer.
[0056] The present application does not limit the amount of carbon source added. In the embodiment of the present application, the mass ratio of the layered positive electrode material body to the carbon source is 90:10 to 99:1, for example, it can be 90:10, 97:3, 94:6, 92:10, 93:10, 94:10, 95:10, 96:10, 97:10, 98:10, 99:10, 99:1, 99:10, 98:10, 97:10, 96:10, 95:10, 94:10, 93:10, 92:10, 91:10, etc. If the ratio of the carbon source mixed during ball milling is too high, the passivation layer formed will be too thick, which will lead to the deterioration of the initial dynamic performance of the battery; if the ratio of the carbon source is too small, the passivation film formed will be insufficient and cannot effectively protect the surface of the positive electrode material. Under the above ratio of 90:10 to 99:1, the carbon layer formed is more uniform, the thickness is moderate, and the protective effect is obvious. Further, the mass ratio of the layered positive electrode material body to the carbon source is 98:2 to 95:5. Under the above conditions, the thickness of the passivation film is better. Furthermore, the mass ratio of the layered positive electrode material body to the carbon source is 97:3. Under the above ratio, the formed carbon layer is the most uniform and has a moderate thickness. It can effectively avoid the side reactions caused by the contact between the positive electrode material and the electrolyte while ensuring that the positive electrode material has a high energy density, and can ensure that the positive electrode material has a low surface impedance, so that the passivation layer is within a suitable range, which can ensure that the secondary battery has a high energy density, good cycle performance and a long cycle life, and the protective effect is most obvious.
[0057] In addition, specifically, step S10 includes:
[0058] The layered cathode material body and the carbon source are mixed, a grinding aid is added, the mixture is ball-milled, and then dried to obtain an intermediate.
[0059] In order to increase the fluidity of the carbon source during ball milling and help the carbon source form a more complete coating layer on the surface of the positive electrode material, it is necessary to add a grinding aid during ball milling. The grinding aid is an organic grinding aid with better fluidity. Specifically, in an embodiment of the present application, the grinding aid includes at least one of alcohol, acetone, benzene and ether.
[0060] Alcohol is ethanol, which is volatile; acetone (CH3COCH3), also known as dimethyl ketone, is the simplest saturated ketone; benzene (C6H6) is an organic compound, which is the simplest aromatic hydrocarbon in composition structure. It is a colorless, sweet, oily transparent liquid at room temperature; ether is an organic compound with the chemical formula C2H5OC2H5, which is a colorless transparent liquid with a special pungent smell. It has a sweet taste; the above four organic compounds are easy to obtain, and after calcination, they burn to generate carbon dioxide and water, and will not introduce new impurities into the positive electrode material.
[0061] The present application does not impose any restriction on the ball milling time. In the embodiments of the present application, the ball milling time is 3 to 7 hours, for example, it can be 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, etc. The above ball milling time can ensure that the positive electrode material particles are completely coated. Furthermore, the ball milling time is 3 to 5 hours, and further, the ball milling time is 4 hours. In this way, the coating effect is the best.
[0062] The present application does not limit the drying conditions. In the embodiments of the present application, the drying conditions are vacuum drying at 80° C. and drying time of 12 hours to ensure complete drying.
[0063] The present application does not limit the amount of grinding aid added. In the embodiments of the present application, the mass ratio of the carbon source to the grinding aid is 95:5 to 99.5:0.5, for example, it can be 95:5, 98.5:1.5, 99.5:0.5, 95:4, 95:3, 95:2, 95:1, 95:0.5, 99.5:5, 99.5:4, 99.5:3, 99.5:2, 99.5:1, etc. Experiments show that under the above ratio, the fluidity of the carbon source during ball milling can be better increased, and the carbon source can be helped to form a more complete coating layer on the surface of the positive electrode.
[0064] Furthermore, the mass ratio of the carbon source to the grinding aid is 99:1 to 97:3. Furthermore, the mass ratio of the carbon source to the grinding aid is 98.5:1.5, which can best increase the fluidity of the carbon source during ball milling, help the carbon source to form a more complete coating layer on the positive electrode surface, and thus best alleviate the phase change on the surface of the positive electrode material and increase the life of the positive electrode material.
[0065] S20, calcining the intermediate to obtain a positive electrode material.
[0066] In this step, the intermediate is calcined to obtain a completely coated passivation layer, so that a spinel layer is formed in situ on the surface of the layered positive electrode material body, and the carbon source also generates a carbon layer at high temperature. It can be seen that in this step, the selection of calcination conditions is crucial to the formation of the passivation film.
[0067] In an embodiment of the present application, the calcination is carried out in an air atmosphere; during calcination, the heating rate is 5-15°C / 5in, for example, it can be 5°C / 5in, 6°C / 5in, 7°C / 5in, 8°C / 5in, 9°C / 5in, 10°C / 5in, 11°C / 5in, 12°C / 5in, 13°C / 5in, 14°C / 5in, 15°C / 5in, etc.; the calcination temperature is 400-700°C, for example, it can be 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, etc.; the calcination time is 30-1205in, for example, it can be 305in, 405in, 505in, 605in, 705in, 805in, 905in, 1005in, 1105in, 1205in, etc. During calcination, if the heating rate is too fast, the temperature is too high, or the time is too long, the organic matter will be completely converted into carbon dioxide and the outermost carbon layer cannot be retained; if the heating rate is too slow, the temperature is too low, or the time is too short, the organic matter will not be completely calcined, deteriorating the interface performance. Under the above conditions, a uniform and stable passivation layer can be obtained.
[0068] It can be understood that the above three conditions of heating rate, calcination temperature and calcination time can be met at the same time, or only one of them can be met. As an embodiment of the present application, the above three conditions are met at the same time, so that the obtained passivation layer is more uniform and stable.
[0069] As a more preferred embodiment of the present application, the calcination conditions are: in an air atmosphere, a heating rate of 10 to 13°C / 5in, keeping warm at a temperature of 500 to 600°C for 50 to 755in, and obtaining a surface passivated positive electrode material after natural cooling.
[0070] As the optimal embodiment of the present application, the calcination conditions are: in an air atmosphere, a heating rate of 10°C / 5in, keeping warm at a temperature of 550°C for 505in, and obtaining a surface passivated positive electrode material after natural cooling.
[0071] By the same token, the three conditions of heating rate, calcination temperature and calcination time can be met at the same time, or only one of them can be met. As an embodiment of the present application, the above three conditions are met at the same time, so that the passivation layer obtained is the most uniform and stable.
[0072] In the present application, a carbon source is selected and mixed with a layered positive electrode material by ball milling, and a grinding aid is added during ball milling, so that a more complete coated passivation layer can be obtained after calcination. The passivation layer is a spinel phase structure layer and an outermost carbon layer from the inside to the outside, and a composite passivation layer composed of a high-pressure resistant spinel phase structure layer and an outermost carbon layer can alleviate the erosion of the electrolyte, reduce oxygen release and surface phase change, and ultimately extend the life of the positive electrode material and alleviate the growth of DC impedance. In addition, the present application adopts a solid phase mixing method of ball milling, which is simple and easy to control, can be industrialized on a large scale, and has good application prospects.
[0073] It can be understood that the preparation method of the positive electrode material proposed in the present application has all the beneficial effects of the above-mentioned positive electrode materials, which will not be described one by one here.
[0074] In a third aspect, the present application provides a positive electrode plate, comprising the positive electrode material in the embodiment of the first aspect or the positive electrode material prepared in the embodiment of the second aspect.
[0075] As an example, the positive electrode sheet includes a current collector and a positive electrode coating disposed on at least one surface of the current collector, the current collector has two surfaces opposite to each other in its own thickness direction, and the positive electrode coating is disposed on any one or both of the two opposite surfaces of the current collector. The current collector includes aluminum foil and other commonly used positive electrode current collectors.
[0076] The positive electrode coating includes a positive electrode active material, a binder and a conductive agent. The positive electrode active material includes the positive electrode material in the first embodiment of the present application or the positive electrode material prepared in the second embodiment. The binder includes but is not limited to polyvinylidene fluoride, a copolymer of vinylidene fluoride-hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, carboxymethyl cellulose sodium, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene, polyhexafluoropropylene and at least one of styrene-butadiene rubber, and the mass content of the binder is selected in the range of 0.5% to 3%. The conductive agent includes but is not limited to at least one of carbon black (SP), carbon nanotubes (CNT), and graphene. In order to increase the conductivity of the positive electrode sheet, the mass content of the conductive agent ranges from 0.8% to 4%.
[0077] The positive electrode plate proposed in this application has all the beneficial effects of the above-mentioned positive electrode materials, which will not be described in detail here.
[0078] In a fourth aspect, the present application provides a secondary battery, comprising the positive electrode plate in the above embodiment.
[0079] The secondary battery proposed in the present application takes a lithium-ion battery as an example. The lithium-ion battery includes the positive electrode sheet, the negative electrode sheet, the isolation membrane and the electrolyte in the embodiment of the third aspect of the present application.
[0080] As an example, the negative electrode sheet includes a current collector and a negative electrode coating. The current collector includes copper foil and other commonly used negative electrode current collectors. The negative electrode coating includes a negative electrode active material, a binder and a conductive agent. The conductive agent and the binder are similar to the conductive agent and the binder of the positive electrode coating, respectively, and the negative electrode active material includes but is not limited to at least one of soft carbon, hard carbon, interphase carbon microspheres (MCMB), silicon, silicon-carbon composites, lithium titanate, alloys, artificial graphite and natural graphite. The separator includes a polyethylene (PE) separator and a polypropylene (PP) separator. The electrolyte includes at least two of dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), ethylene carbonate (EC), propylene carbonate (PC), and propyl propionate (PP). In addition, the electrolyte may also additionally include at least one of vinylene carbonate (VC), fluoroethylene carbonate (FEC) and dinitrile compounds as electrolyte additives, wherein the dinitrile compound includes succinonitrile (SN).
[0081] The positive electrode sheet, negative electrode sheet and isolation film described in the third aspect of the present application are prepared into a bare battery cell by winding or stacking, and then added to an external shell such as an aluminum-plastic film, an aluminum shell or a steel shell. After adding the electrolyte and going through a series of processes such as formation and sealing, a lithium-ion battery is prepared.
[0082] The secondary battery proposed in the present application includes the positive electrode plate in the above embodiment, and the positive electrode plate includes the positive electrode material in the above embodiment. Therefore, the secondary battery has all the beneficial effects of the above positive electrode material, which will not be described one by one here.
[0083] Specifically, at least one secondary battery constitutes a battery module, and those skilled in the art may adaptively select the specific number of secondary batteries according to the application and capacity of the battery module.
[0084] In addition, when there are more than two secondary batteries in the battery module, the two or more secondary batteries can be arranged in sequence along the length direction of the battery module. Of course, they can also be arranged in any other manner, which is not limited by the present application.
[0085] At least one battery module constitutes a battery pack, and the specific number of battery modules can be adaptively selected by those skilled in the art according to the application and capacity of the battery pack.
[0086] In a fifth aspect, the present application provides an electrical device, including the secondary battery in the above embodiment. The secondary battery can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, tablet computers, e-books, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric buses, electric trucks, etc.), ships and satellites, energy storage systems, etc., but are not limited thereto.
[0087] The electrical device proposed in the present application, including the positive electrode material as described above, possesses all the beneficial effects of the positive electrode material as described above, which will not be described one by one here.
[0088] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments and drawings. It should be understood that the following embodiments are only used to explain the present invention, and are not used to limit the present invention.
[0089] The conditions of each embodiment are shown in Table 1:
[0090] Table 1 Conditions of Examples 1 to 17
[0091]
[0092]
[0093] Example 1
[0094] (1) Ball milling: Li(Ni 0.5 Co 0.1 Mn 0.4 ) The O2 layered cathode material and stearic acid were weighed in a mass ratio of 97:3, and then added to a ball mill. At the same time, alcohol grinding aid was added in a mass ratio of stearic acid to alcohol of 98.5:1.5, and ball milling was performed for 4 hours. The mixed material after ball milling was vacuum dried at 80°C for 12 hours to obtain an intermediate;
[0095] (2) Calcination treatment: The intermediate after ball milling and drying is heated at a rate of 10°C / 5in in an air atmosphere, kept at 550°C for 505in, and naturally cooled to obtain a surface passivated positive electrode material.
[0096] Example 2
[0097] (1) Ball milling: Li(Ni 0.5 Co 0.1 Mn 0.4) The O2 layered cathode material and oleic acid were weighed in a mass ratio of 97:3, and then added to a ball mill. At the same time, alcohol grinding aid was added in a mass ratio of stearic acid to alcohol of 98.5:1.5, and ball milling was performed for 4 hours. The mixed material after ball milling was vacuum dried at 80°C for 12 hours to obtain an intermediate;
[0098] (2) Calcination treatment: The intermediate after ball milling and drying is heated at a rate of 10°C / 5in in an air atmosphere, kept at 550°C for 505in, and naturally cooled to obtain a surface passivated positive electrode material.
[0099] Example 3
[0100] (1) Ball milling: Li(Ni 0.5 Co 0.1 Mn 0.4 ) The O2 layered cathode material and stearic acid were weighed in a mass ratio of 90:10, and then added to a ball mill. At the same time, alcohol grinding aid was added in a mass ratio of stearic acid to alcohol of 98.5:1.5, and ball milling was performed for 4 hours. The mixed material after ball milling was vacuum dried at 80°C for 12 hours to obtain an intermediate;
[0101] (2) Calcination treatment: The intermediate after ball milling and drying is heated at a rate of 10°C / 5in in an air atmosphere, kept at 550°C for 505in, and naturally cooled to obtain a surface passivated positive electrode material.
[0102] Example 4
[0103] (1) Ball milling: Li(Ni 0.5 Co 0.1 Mn 0.4 ) The O2 layered cathode material and stearic acid were weighed in a mass ratio of 99:1, and then added to a ball mill. At the same time, alcohol grinding aid was added in a mass ratio of stearic acid to alcohol of 98.5:1.5, and ball milling was performed for 4 hours. The mixed material after ball milling was vacuum dried at 80°C for 12 hours to obtain an intermediate;
[0104] (2) Calcination treatment: The intermediate after ball milling and drying is heated at a rate of 10°C / 5in in an air atmosphere, kept at 550°C for 505in, and naturally cooled to obtain a surface passivated positive electrode material.
[0105] Example 5
[0106] (1) Ball milling: Li(Ni 0.5 Co 0.1 Mn 0.4) The O2 layered cathode material and stearic acid were weighed in a mass ratio of 97:3, and then added to a ball mill. At the same time, alcohol grinding aid was added in a mass ratio of stearic acid to alcohol of 99.5:0.5, and ball milling was performed for 4 hours. The mixed material after ball milling was vacuum dried at 80°C for 12 hours to obtain an intermediate;
[0107] (2) Calcination treatment: The intermediate after ball milling and drying is heated at a rate of 10°C / 5in in an air atmosphere, kept at 550°C for 505in, and naturally cooled to obtain a surface passivated positive electrode material.
[0108] Example 6
[0109] (1) Ball milling: Li(Ni 0.5 Co 0.1 Mn 0.4 ) The O2 layered cathode material and stearic acid were weighed in a mass ratio of 97:3, and then added to a ball mill. At the same time, an alcohol grinding aid was added in a mass ratio of stearic acid to alcohol of 95:5, and ball milling was performed for 4 hours. The mixed material after ball milling was vacuum dried at 80°C for 12 hours to obtain an intermediate;
[0110] (2) Calcination treatment: The intermediate after ball milling and drying is heated at a rate of 10°C / 5in in an air atmosphere, kept at 550°C for 505in, and naturally cooled to obtain a surface passivated positive electrode material.
[0111] Example 7
[0112] (1) Ball milling: Li(Ni 0.5 Co 0.1 Mn 0.4 ) The O2 layered cathode material and stearic acid were weighed in a mass ratio of 97:3, and then added to a ball mill. At the same time, alcohol grinding aid was added in a mass ratio of stearic acid to alcohol of 98.5:1.5, and ball milling was performed for 4 hours. The mixed material after ball milling was vacuum dried at 80°C for 12 hours to obtain an intermediate;
[0113] (2) Calcination treatment: The intermediate after ball milling and drying is heated at a rate of 10°C / 5in in an air atmosphere, kept at 700°C for 505in, and naturally cooled to obtain a surface passivated positive electrode material.
[0114] Example 8
[0115] (1) Ball milling: Li(Ni 0.5 Co 0.1 Mn 0.4) The O2 layered cathode material and stearic acid were weighed in a mass ratio of 97:3, and then added to a ball mill. At the same time, acetone was added as a grinding aid in a mass ratio of stearic acid to acetone of 98.5:1.5, and ball milling was performed for 4 hours. The mixed material after ball milling was vacuum dried at 80°C for 12 hours to obtain an intermediate;
[0116] (2) Calcination treatment: The intermediate after ball milling and drying is heated at a rate of 10°C / 5in in an air atmosphere, kept at 550°C for 505in, and naturally cooled to obtain a surface passivated positive electrode material.
[0117] Example 9
[0118] (1) Ball milling: 0.5Li2MnO3·0.5Li(Ni 1 / 3 Co 1 / 3 Mn 1 / 3 ) The O2 layered cathode material and stearic acid were weighed in a mass ratio of 97:3, and then added to a ball mill. At the same time, alcohol grinding aid was added in a mass ratio of stearic acid to alcohol of 98.5:1.5, and ball milling was performed for 4 hours. The mixed material after ball milling was vacuum dried at 80°C for 12 hours to obtain an intermediate;
[0119] (2) Calcination treatment: The intermediate after ball milling and drying is heated at a rate of 10°C / 5in in an air atmosphere, kept at 550°C for 505in, and naturally cooled to obtain a surface passivated positive electrode material.
[0120] Example 10
[0121] (1) Ball milling: LiCoO2 layered cathode material and stearic acid were weighed in a mass ratio of 97:3, and then added to a ball mill. At the same time, alcohol grinding aid was added in a mass ratio of stearic acid to alcohol of 98.5:1.5, and ball milling was performed for 4 hours. The mixed material after ball milling was vacuum dried at 80°C for 12 hours to obtain an intermediate;
[0122] (2) Calcination treatment: The intermediate after ball milling and drying is heated at a rate of 10°C / 5in in an air atmosphere, kept at 550°C for 505in, and naturally cooled to obtain a surface passivated positive electrode material.
[0123] Embodiment 11
[0124] (1) Ball milling: Li(Ni 0.5 Co 0.1 Mn 0.4) The O2 layered cathode material and the long-chain organic acid (mixture of stearic acid and oleic acid, the mass ratio of the two is 1:1) are weighed at a mass ratio of 97:3, and then added to a ball mill. At the same time, an alcohol grinding aid is added at a mass ratio of stearic acid to alcohol of 98.5:1.5, and ball milling is performed for 4 hours. The mixed material after ball milling is vacuum dried at 80°C for 12 hours to obtain an intermediate;
[0125] (2) Calcination treatment: The intermediate after ball milling and drying is heated at a rate of 10°C / 5in in an air atmosphere, kept at 550°C for 505in, and naturally cooled to obtain a surface passivated positive electrode material.
[0126] Example 12
[0127] (1) Ball milling: Li(Ni 0.5 Co 0.1 Mn 0.4 ) The O2 layered cathode material and stearic acid were weighed in a mass ratio of 97:3, and then added to a ball mill. At the same time, a grinding aid (a mixture of alcohol and acetone, the mass ratio of the two being 1:1) was added in a mass ratio of 98.5:1.5, and ball milling was performed for 4 hours. The mixed material after ball milling was vacuum dried at 80°C for 12 hours to obtain an intermediate;
[0128] (2) Calcination treatment: The intermediate after ball milling and drying is heated at a rate of 10°C / 5in in an air atmosphere, kept at 550°C for 505in, and naturally cooled to obtain a surface passivated positive electrode material.
[0129] Example 13
[0130] (1) Put Li(Ni 0.5 Co 0.1 Mn 0.4 ) The O2 layered cathode material body and stearic acid are mixed in a mass ratio of 97:3;
[0131] (2) Calcination treatment: The material in (1) is heated at a rate of 10°C / 5in in an air atmosphere, kept at 550°C for 505in, and cooled naturally to obtain a surface passivated positive electrode material.
[0132] (That is, except that ball milling is not performed, the remaining steps and conditions are the same as those in Example 1).
[0133] Embodiment 14
[0134] (1) Ball milling: Li(Ni 0.5 Co 0.1 Mn 0.4) The O2 layered cathode material and stearic acid were weighed in a mass ratio of 97:3, and then added to a ball mill. At the same time, alcohol grinding aid was added in a mass ratio of stearic acid to alcohol of 98.5:1.5, and ball milling was performed for 3 hours. The mixed material after ball milling was vacuum dried at 80°C for 12 hours to obtain an intermediate;
[0135] (2) Calcination treatment: The intermediate after ball milling and drying is heated at a rate of 10°C / 5in in an air atmosphere, kept at 550°C for 505in, and naturally cooled to obtain a surface passivated positive electrode material.
[0136] Embodiment 15
[0137] (1) Ball milling: Li(Ni 0.5 Co 0.1 Mn 0.4 ) The O2 layered cathode material and stearic acid were weighed in a mass ratio of 97:3, and then added to a ball mill. At the same time, alcohol grinding aid was added in a mass ratio of stearic acid to alcohol of 98.5:1.5, and ball milling was performed for 7 hours. The mixed material after ball milling was vacuum dried at 80°C for 12 hours to obtain an intermediate;
[0138] (2) Calcination treatment: The intermediate after ball milling and drying is heated at a rate of 10°C / 5in in an air atmosphere, kept at 550°C for 505in, and naturally cooled to obtain a surface passivated positive electrode material.
[0139] Example 16
[0140] (1) Ball milling: Li(Ni 0.5 Co 0.1 Mn 0.4 ) The O2 layered cathode material and stearic acid were weighed in a mass ratio of 97:3, and then added to a ball mill. At the same time, alcohol grinding aid was added in a mass ratio of stearic acid to alcohol of 98.5:1.5, and ball milling was performed for 4 hours. The mixed material after ball milling was vacuum dried at 80°C for 12 hours to obtain an intermediate;
[0141] (2) Calcination treatment: The intermediate after ball milling and drying is heated at a rate of 5°C / 5in in an air atmosphere, kept at 400°C for 1205in, and naturally cooled to obtain a surface passivated positive electrode material.
[0142] Embodiment 17
[0143] (1) Ball milling: Li(Ni 0.5 Co 0.1 Mn 0.4) The O2 layered cathode material and stearic acid were weighed in a mass ratio of 97:3, and then added to a ball mill. At the same time, alcohol grinding aid was added in a mass ratio of stearic acid to alcohol of 98.5:1.5, and ball milling was performed for 4 hours. The mixed material after ball milling was vacuum dried at 80°C for 12 hours to obtain an intermediate;
[0144] (2) Calcination treatment: The intermediate after ball milling and drying is heated at a rate of 15°C / 5in in an air atmosphere, kept at a temperature of 550°C for 305in, and naturally cooled to obtain a surface passivated positive electrode material.
[0145] Comparative Example 1
[0146] Except that step (2) is not performed, the remaining steps and conditions are the same as those in Example 1.
[0147] The intermediate obtained in step (1) and the surface passivated positive electrode material obtained in step (2) of Example 1 of the present invention were subjected to scanning electron microscopy, respectively, and the corresponding Figure 1 and Figure 2 ,Depend on Figure 1 It can be seen that after ball milling and mixing with the carbon source stearic acid, the surface of the layered cathode material is coated with a complete layer of stearic acid. Figure 2 It shows that a thin carbon layer remains on the surface after calcination, and the carbon content is about 0.8% as tested by CS analyzer. It can be seen that the carbon layer on the surface of the layered positive electrode material body has been successfully prepared.
[0148] XRD patterns of the surface passivated positive electrode materials obtained in Example 1 and Example 13 of the present invention were obtained. Figure 3 ,Depend on Figure 3 It can be seen that compared with the (101) crystal plane of the XRD of the positive electrode material without ball milling treatment in Example 13, a spinel signal is obtained after passivation treatment, which shows that ball milling is more important for the formation of the spinel layer.
[0149] Preparation of secondary batteries
[0150] The positive electrode materials obtained in Examples 1 to 17 and Comparative Example 1 were coated into pole pieces, used as positive electrodes, and lithium sheets were used as negative electrodes to assemble button-type batteries, which were charged and discharged in the voltage range of 2.5 to 4.45 V. The cycle data graphs of Examples 1 and 13 are shown in FIG. Figure 4 The carbon content, initial impedance relative value, impedance growth rate after 50 cycles, and capacity retention rate after 50 cycles of the obtained positive electrode material were determined, and Table 2 was obtained.
[0151] Carbon content determination: STA300 synchronous thermogravimetric analyzer was used to test the carbon content.
[0152] Impedance value test: The CHI660E electrochemical workstation was used to perform the EIS test to obtain the initial and cycle impedance of the battery, with an amplitude of 55 V and a frequency of 300 kHz to 30 5 Hz.
[0153] Capacity retention rate test after 50 cycles: The cycle test was carried out using a Xinwei charge and discharge tester with a voltage range of 2.5-4.45V and a charge and discharge rate of 0.5C / 1C.
[0154] Table 2 Performance test of positive electrode materials
[0155]
[0156] From Table 1 and Figure 1 It can be seen that, from the comparison of the data of the embodiments and the comparative examples, the retention rates of the positive electrode materials prepared in embodiments 1 to 17 are all high after 50 cycles. Compared with embodiment 1, the carbon source used in embodiment 2 is oleic acid. Since the coating property of oleic acid is not as strong as that of stearic acid in embodiment 1, the carbon content of the positive electrode material in embodiment 2 is reduced; the capacity retention rate of the positive electrode material obtained by ball milling without coating in embodiment 13 after 50 cycles is 51%, and the capacity retention rate of the original positive electrode material without calcination treatment in comparative example 1 after 50 cycles is only 46%, indicating that ball milling and calcination are crucial to the preparation of the positive electrode material of the present application. The use of carbon source and positive electrode material for ball milling can ensure that the positive electrode material particles are completely coated, and a more complete and dense passivation layer is formed after calcination, which has a better performance improvement effect; adding a grinding aid can increase the fluidity of the carbon source during ball milling, help the carbon source and the positive electrode material to mix better, and finally form a completely covered organic acid polymer coating layer on the positive electrode surface, thereby obtaining a more complete passivation layer after calcination.
[0157] In addition, generally speaking, the smaller the initial impedance relative value and the impedance growth rate after 50 cycles, the better, and the greater the capacity retention rate after 50 cycles, the better. Combining the above three factors, it can be concluded through comparison that the positive electrode material performance of Example 1 is the best.
[0158] In summary, the present application uses a carbon source and a layered positive electrode material for ball milling and mixing, and a grinding aid is added during ball milling, so that a more complete coated passivation layer can be obtained after calcination. The passivation layer is a spinel phase structure layer and an outermost carbon layer from the inside to the outside. The composite passivation layer composed of a high-pressure resistant spinel phase structure layer and an outermost carbon layer can alleviate the erosion of the electrolyte, reduce oxygen release and surface phase change, and ultimately extend the life of the positive electrode material and alleviate the growth of DC impedance. In addition, the present application adopts a solid-phase mixing method of ball milling, which is simple and easy to control, can be industrialized on a large scale, and has good application prospects.
[0159] The above are only preferred embodiments of the present invention, and do not limit the patent scope of the present invention. For those skilled in the art, the present invention may have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the patent protection scope of the present invention.
Claims
1. A positive electrode material, characterized in that: include: A layered positive electrode material body and a passivation layer coated outside the layered positive electrode material body, wherein the passivation layer comprises a spinel layer and a carbon layer stacked sequentially from inside to outside; The material of the layered positive electrode material body includes LiMO2, wherein M is Co, or M is at least one of Mn, Ni, Fe, Al, Nb, Ti, Zr, W, V, Ta, Mo, Sb and La as well as Co.
2. The positive electrode material according to claim 1, characterized in that The carbon content of the positive electrode material is 0.02wt.% to 3.20wt.%.
3. A method for preparing a positive electrode material as claimed in claim 1 or 2, characterized in that: The following steps are involved: S10, mixing the layered cathode material body and the carbon source to obtain an intermediate; S20, calcining the intermediate to obtain a positive electrode material.
4. The method for preparing the positive electrode material according to claim 3, characterized in that: In step S10, the carbon source includes a long-chain organic acid.
5. The method for preparing the positive electrode material according to claim 4, characterized in that: The long-chain organic acid includes at least one of stearic acid, oleic acid, linoleic acid, linolenic acid, palmitic acid and arachidonic acid.
6. The method for preparing the positive electrode material according to claim 3, characterized in that: In step S10, the mass ratio of the layered positive electrode material body to the carbon source is 90:10 to 99:
1.
7. The method for preparing the positive electrode material according to claim 3, characterized in that: In step S10, the mass ratio of the layered positive electrode material body to the carbon source is 98:2 to 95:
5.
8. The method for preparing the positive electrode material according to claim 3, characterized in that: Step S10 includes: mixing the layered positive electrode material body and the carbon source, adding a grinding aid, ball milling the mixture, and drying to obtain an intermediate.
9. The method for preparing the positive electrode material according to claim 8, characterized in that: The grinding aid comprises at least one of alcohol, acetone, benzene and ether; and / or, The mass ratio of the carbon source to the grinding aid is 95:5 to 99.5:0.5; and / or, The ball milling time is 3 to 7 hours.
10. The method for preparing the positive electrode material according to claim 8, characterized in that: The mass ratio of the carbon source to the grinding aid is 99:1 to 97:3; and / or, The ball milling time is 3 to 5 hours.
11. The method for preparing the positive electrode material according to claim 3, characterized in that: In step S20, The calcination is carried out in an air atmosphere; and / or, During calcination, the heating rate is 5 to 15°C / min; and / or, The calcination temperature is 400-700° C.; and / or, The calcination time is 30 to 120 minutes.
12. The method for preparing the positive electrode material according to claim 3, characterized in that: In step S20, During calcination, the heating rate is 10-13°C / min; and / or, The calcination temperature is 500-600° C.; and / or, The calcination time is 50 to 75 minutes.
13. A positive electrode sheet, characterized in that: Comprising the positive electrode material as claimed in claim 1 or 2.
14. A secondary battery, characterized in that: Comprising the positive electrode sheet as described in claim 13.
15. An electrical device, characterized in that: Includes the secondary battery as claimed in claim 14.
Citation Information
Patent Citations
Lithium-rich manganese-based composite positive electrode material and preparation method and application thereof
CN114665070A